HUBUNGAN ANTARA GEJALA MENOPAUSE DENGAN KUALITAS HIDUP PEREMPUAN KLIMAKTERIK - Trisetiyaningsih, Yanita (Jurnal Kesehatan Samodra Ilmu (JKSI), 2016)
Background: World Health Organization (WHO) defines the climacteric as a phase where there is a transition between the reproductive phase to the non-reproductive phase. At the time this will happen climacteric hormonal changes in women. Physical and psychological changes during climacterium phase could influence quality of life in climacteric women. Eighty percent of the women reported any discomfort that occurs when the climacteric symptoms such as headaches, sexual problems, tachycardia, hot flushes, sweating and insomnia that can significantly decrease the quality of live Purpose: The purpose of the study was correlation between menopausal symptom with quality of life in climacteric women. Methods: The study was quantitave research which cross sectional design. In this study population to be used are all climacteric women aged 45-60 years in Gamping Kidul Ambarketawang Gamping Sleman, Yogyakarta. Sampling was done by simple random sampling method.The sample was 88 subjects Data collection used Menopause Rating Scale (MRS) and the WHOQOL-BREF. The analysis used is Spearman rank correlation test. Result: The most frequent symptoms of 11 composing the MRS (n-88) was muscle and joint problems (78.6%). 44 (50%) experienced mild menopausal symptoms, 32 (36.4%) had moderate symptoms of menopause. Quality of life for the majority of respondents have a good quality of life for as many as 59 (67.1%)There is a significant relationship between menopausal symptoms with quality of life (p<0,05).